SIMULASI RANCANGAN UNTUK SATELIT MIKRO - Rizal, Sofian; Farmasiantoro, Adi (Majalah Ilmiah Matematika Komputer, 2006)
Micro satellite is a try-out satellite with Store and Forward communication, image projection wide angle camera and satellite control system. Micro satellite combine this use TT&C, OBC, PAYLOAD and POWER, solar cell and radio communication. Language program used is C language program on NOS operating system. Micro satellite plan this destination for make small satellite with cheap by special quality.